The effect of season and the introduction of rams on oestrous activity in Somali, Nandi, Merino, Karakul and New Zealand Romney Marsh ewes in Kenya - Carles, A.B.; Kipngeno, W.A.K. (Cambridge University Press, 1986)
A study was made of the levels of oestrous activity of two indigenous breeds of sheep (Somali and Nandi) and three exotic breeds of sheep (Merino, Karakul and New Zealand Romney Marsh) over a period of 3 years, in an equatorial environment. Breed was the only significant source of variation for the length of the oestrous cycle (P < 0.01). The mean lengths of the oestrous cycle were 17.2 (s.d. 3.21), 17.5 (s.d. 2.24), 17.9 (s.d. 2.99), 17.5 (s.d. 2.57) and 16.5 (s.d. 3.41) days for the Somali, Nandi, Merino, Karakul and Romney Marsh breeds, respectively. The mean percentage of ewes of the different breeds showing oestrus in 20-day periods were 69.8 (s.d. 22.57), 49.9 (s.d. 18.67), 63.4 (s.d. 25.70), 79.2 (s.d. 20.30) and 33.2 (s.d. 23.50) % for the Somali, Nandi, Merino, Karakul and Romney Marsh breeds, respectively. Time-series analysis did not detect any evidence of seasonal variation in oestrous activity, although there was an indication that the Merino and Romney Marsh breeds showed a marked increase in oestrous activity following the introduction of rams. It was concluded that the variation in level of oestrous activity was short term and random.